2017
DOI: 10.26493/1854-6935.15.231-254
|View full text |Cite
|
Sign up to set email alerts
|

The Unemployment-Stock Market Relationship in South Africa: Evidence from Symmetric and Asymmetric Cointegration Models

Abstract: In this study, we examine linear and nonlinear cointegration and causal relations between unemployment and stock market returns in South Africa using quarterly data collected between 1994:q1 and 2016:q1. Our empirical results reveal significant cointegration effects between the time series in both linear and nonlinear models, even though both frameworks ultimately reject the notion of any causal relations between the variables. Collectively, our study rejects the notion of unemployment being a good predictor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…This hinges on the grounds that improvement in economic growth causes the demand for tourism to rise and vice versa (Narayan, 2004;Sari Hassoun et al, 2021). This conservation hypothesis has been analyzed and verified by several studies, including Sari Hassoun et al (2021) for Algeria; Aratuo and Estienne (2019) for the United States; Phiri (2016) for South Africa; Bouzahzah and Menyari (2013) for Morocco and Tunisia; Ivanov and Webster (2013) for a worldwide investigation; Lee (2012) for Singapore; and Oh (2005) for Korea. Oh (2005) explored the tourism development-economic growth nexus in Korea using the Engle-Granger 2-stage technique and a VAR model.…”
Section: Literature Reviewmentioning
confidence: 73%
“…This hinges on the grounds that improvement in economic growth causes the demand for tourism to rise and vice versa (Narayan, 2004;Sari Hassoun et al, 2021). This conservation hypothesis has been analyzed and verified by several studies, including Sari Hassoun et al (2021) for Algeria; Aratuo and Estienne (2019) for the United States; Phiri (2016) for South Africa; Bouzahzah and Menyari (2013) for Morocco and Tunisia; Ivanov and Webster (2013) for a worldwide investigation; Lee (2012) for Singapore; and Oh (2005) for Korea. Oh (2005) explored the tourism development-economic growth nexus in Korea using the Engle-Granger 2-stage technique and a VAR model.…”
Section: Literature Reviewmentioning
confidence: 73%
“…Ketenci (2016) found lower saving retention coefficient and thus, higher international capital mobility in the post-Asian crisis period. In another study, Phiri (2017) found increase in international capital mobility in the post-global financial crisis period thereby weakening the F–H high correlation between domestic savings and investment. Therefore, countries with higher international capital mobility are likely to be affected by the contagion effects of global financial crisis.…”
Section: Literature Reviewmentioning
confidence: 93%
“…The first one is that it is believed that financial market indicator, as well as unemployment, behaves asymmetrically throughout different economic conditions. Thus, modelling financial development and growth or unemployment linearly may yield low explanatory or testing power and an inferior coefficient (Tapa, et al 2016). Second, the economic agents are said to respond differently to positive development in the financial sector than negative development in the financial sector.…”
Section: Empirical Reviewmentioning
confidence: 99%